2016
DOI: 10.1073/pnas.1524484113
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and circadian variation of sleep and alertness in men vs. naturally cycling women

Abstract: This study quantifies sex differences in the diurnal and circadian variation of sleep and waking while controlling for menstrual cycle phase and hormonal contraceptive use. We compared the diurnal and circadian variation of sleep and alertness of 8 women studied during two phases of the menstrual cycle and 3 women studied during their midfollicular phase with that of 15 men. Participants underwent an ultradian sleep-wake cycle (USW) procedure consisting of 36 cycles of 60-min wake episodes alternating with 60-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 39 publications
4
51
0
Order By: Relevance
“…All of these findings are compatible with those provided by previous studies, where women are more likely than men to report more sleep problems and poor sleep quality [58,59]. Similarly, other studies [60] report that, for a similar sleep schedule in men and women, women's chronobiological cycle makes them sleep and wake up before men.…”
Section: Discussionsupporting
confidence: 90%
“…All of these findings are compatible with those provided by previous studies, where women are more likely than men to report more sleep problems and poor sleep quality [58,59]. Similarly, other studies [60] report that, for a similar sleep schedule in men and women, women's chronobiological cycle makes them sleep and wake up before men.…”
Section: Discussionsupporting
confidence: 90%
“…Hormonal changes might act as modulators for an aging circadian system, causing a slow-down in women between 35 and 50 (and a speed-up in men aged 55 to 65). Studies examining circadian differences between males and females usually report an earlier phase of core body temperature (CBT) and melatonin rhythms in women than men [34][35][36][37][38]. These studies, conducted with younger subjects (<30yrs), are consistent with our results and previous findings that suggest that women are earlier chronotypes than men during adolescence and early adulthood.…”
Section: Men and Women Are Different Chronotypes-depending On Agesupporting
confidence: 91%
“…Additionally, postmortem studies of men and women with MDD have reported a sex difference in the expression within the dorsolateral prefrontal cortex of multiple glutamatergic genes, with increased expression in women [266]. Finally, several clock genes have been reported to differ in a sex-specific manner, possibly in keeping with reports that women have an overall phase advance in several measures of circadian rhythmicity compared with men [267][268][269].…”
Section: Neural and Gene Network Functionmentioning
confidence: 59%